Design, construction and evaluation of a prototype house for aided self-help low-income housing in Bangkok - Werayudh Santayanondh; Angel, Shlomo; Goede, J.H. de; Kammeier, Hans Detlef; Reader' s Digest Co. (Bangkok : Asian Institute of Technology, 1979)
A row-house model incorporating ethnic Thai architecture and basic low-cost building practices was designed for a self-help housing project in Bangkok. A prototype house was constructed using mostly permanent building materials (cement, wood, steel) and tested for strength structure. 23 applicant families from slum areas within a 10 km. radius of the Building Together Project site completed a questionnaire to provide feedback on acceptability design and willingness to pay for the house which they will build themselves. They also responded to expansion priorities and cost reduction ideas. Using this information, construction costs were evaluated and a cost-reduction analysis was per formed. Recommendations were made for changing the design to meet the housing needs and financial capabilities of the slum dwellers resettling at the project.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Public housing -- Thailand -- Bangkok